2021
DOI: 10.1093/eurpub/ckab159
|View full text |Cite
|
Sign up to set email alerts
|

Precarious employment and health in the context of COVID-19: a rapid scoping umbrella review

Abstract: Background There are widespread concerns that workers in precarious employment have suffered the most in the COVID-19 pandemic and merit special attention. The aim of this rapid scoping umbrella review was to examine what evidence exists about how COVID-19 has affected the health of this highly vulnerable group, and what gaps remain to be investigated. Methods Five databases were searched for systematic or scoping reviews from January 2020 to May 2021. The quality of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
2
50
1
Order By: Relevance
“…Occupational justice is particularly significant today. Ensuring the health and safety at work, specifically among low-wage and non-health-essential occupations, is imperative to effective pandemic management, public health prevention efforts, and protecting a highly vulnerable workforce [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational justice is particularly significant today. Ensuring the health and safety at work, specifically among low-wage and non-health-essential occupations, is imperative to effective pandemic management, public health prevention efforts, and protecting a highly vulnerable workforce [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essential (non-health) occupations, specifically workers in industries such as manufacturing, transportation, construction, food, and agriculture, were considered vital for maintaining the health and safety of the nation. However, the occupational risk of COVID-19 exposure, COVID-19 infection, and poor mental health outcomes have been found to be greater among low-wage and precarious workers in non-health essential occupations [ 5 , 6 ]. Recent data from the Washington State Department of Health found that agriculture, forestry, fishing, and hunting employees tested positive for COVID-19 at higher rates than any other employment category after health care and social assistance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, and related to the previous point, job and income loss along with the associated psychological impact has been concentrated among groups already vulnerable before the pandemic. 5 These groups include workers on zero-contract hours, those in the gig economy but also self-employed workers and small business owners. Governments spent considerable financial resources to protect businesses and workers from the financial shock resulting from the shutdown of the economy.…”
Section: Gabriela Ksinan Jiskrovamentioning
confidence: 99%
“…Baker4 points out that approximately 75% of the US workforce is employed in such occupations and that these occupations tend to be lower-paid. Lastly, and related to the previous point, job and income loss along with the associated psychological impact has been concentrated among groups already vulnerable before the pandemic 5. These groups include workers on zero-contract hours, those in the gig economy but also self-employed workers and small business owners.…”
mentioning
confidence: 91%
“…Several studies have provided evidence on the adverse impact of the COVID-19 pandemic on a wide range of health outcomes and health behaviors [ 1 , 2 , 3 , 4 , 5 ]. Even if they are not actually infected with the coronavirus, individuals tend to assess their health negatively due to various pandemic-related factors, including enhanced uncertainties with employment and income conditions [ 6 , 7 , 8 , 9 , 10 , 11 ] and higher risks of social isolation caused by restricted mobility due to the implementation of lockdowns and social distancing policies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%